Metode Pembelajaran Qiro’ah Muwahadah dalam Menjaga Kefashihan Bacaan Alquran (Studi Kasus di Pondok Pesantren Madrasatul Quran Tebuireng) - Arifin, Moch.; Afidah, Nurul; Rohmah, Hidayatur (Universitas KH. A. Wahab Hasbullah, 2024)
This thesis presents a research study utilizing a case study approach, with a qualitative methodology employed. The focus of the research is on the model, process, facilitators, and barriers of Qiroah Muwahadah learning in maintaining the fluency of Quranic recitation at Pondok Pesantren Madrasatul Quran. Data collection methods included observation, interviews, and documentation. The analysis revealed that K.H. Yusuf Masyhar utilized a systematic and classical learning model in providing Quranic guidance to the students, grouping them during recitation, fashohah, and group mudarosah sessions according to their reading and memorization abilities, yielding results in line with expectations. Many graduates from the pondok have become influential figures in society due to their proficiency in Quranic recitation. Supporting factors in this learning process include the alumni and graduates' desire to preserve Qiroah Muwahadah, strong bonds among alumni in supporting the pondok's programs, community trust in the pondok's reputation, and the high motivation of the students studying there. However, obstacles to the implementation of this learning process include differences in learning reception, the absence of prominent Qiro’ah Muwahhadah figures today, the variety of preferred recitation styles among students, challenges in program execution, and insufficient attention from management to the importance of maintaining the recognized quality of Quranic recitation fluency.